The role of multi-modality imaging for the assessment of left atrium and left atrial appendage: a clinical consensus statement of the European Association of Cardiovascular Imaging (EACVI), European Heart Rhythm Association (EHRA) of the European Society of Cardiology (ESC) - Sade, Leyla Elif; Faletra, Francesco Fluvio; Pontone, Gianluca; Gerber, Bernhard Lothar Marie; Muraru, Denisa; Edvardsen, Thor; Cosyns, Bernard; Popescu, Bogdan A; Klein, Allan; Marwick, Thomas H; Cameli, Matteo; Saric, Muhamed; et al. (European heart journal cardiovascular Imaging, 2025)
Structural, architectural, contractile, or electrophysiological alterations may occur in the left atrium (LA). The concept of LA cardiopathy is supported by accumulating scientific evidence demonstrating that LA remodelling has become a cornerstone diagnostic and prognostic marker. The structure and the function of the LA and left atrial appendage (LAA), which is an integral part of the LA, are key elements for a better understanding of multiple clinical conditions, most notably atrial fibrillation, cardioembolism, heart failure, and mitral valve diseases. Rational use of various imaging modalities is key to obtain the relevant clinical information. Accordingly, this clinical consensus document from the European Association of Cardiovascular Imaging, in collaboration with the European Heart Rhythm Association, provides comprehensive, up-to-date, and evidence-based guidance to cardiologists and cardiac imagers for the best practice of imaging LA and LAA for the diagnosis, management, and prognostication of the patients.
Keywords: Echocardiography; mužské pohlaví; Consensus; Male; Humans; Female; Prognosis; multimodální zobrazování; lidé; echokardiografie; ženské pohlaví; Atrial Appendage; Evropa; fibrilace síní; Heart Atria; kardiologie; prognóza; konsensus; srdeční síně; kardiologické zobrazovací techniky; Europe; síňové ouško; Multimodal Imaging; Societies, Medical; Atrial Fibrillation; Cardiac Imaging Techniques; Cardiology; společnosti lékařské